Prevalence and Correlates of the Concurrence of Autism Spectrum Disorder and Obsessive Compulsive Disorder in Children and Adolescents: A Systematic Review and Meta-Analysis - Claudia Aymerich; Malein Pacho; Ana Catalan; Noorulain Yousaf; Violeta Pérez-Rodríguez; Matthew J. Hollocks; Mara Parellada; Georgina Krebs; Bruce Clark; Gonzalo Salazar de Pablo (Brain Sciences, 2024)
Background: Autism spectrum disorder (ASD) and obsessive compulsive disorder (OCD) are two common and impairing neurodevelopmental conditions with partial symptomatic overlap. The aim of this study is to systematically and meta-analytically examine the following: (i) the prevalence of an OCD diagnosis among young people with ASD, (ii) the prevalence of an ASD diagnosis among young people with OCD, and (iii) the clinical and therapeutic implications of such comorbidity. Method: A multistep literature search was performed from database inception until 17 November 2023. This PRISMA/MOOSE-compliant systematic review, registered in PROSPERO (CRD42023480543), identified studies reporting on the prevalence, sociodemographic, psychopathologic, prognostic, and therapeutic correlates of OCD and ASD concurrence in children and adolescents. A quantitative meta-analysis with random effects was conducted to analyse the pooled prevalence of OCD among samples with a mean age of < 18 years old with ASD and the prevalence of ASD among individuals under 18 with OCD. Sensitivity analyses were performed to investigate the effect of diagnostic criteria and different continents. Meta-regression analyses were conducted to examine the effect of gender, age, IQ, and OCD severity scores. A narrative review of the clinical and therapeutical implications of the comorbidity was provided. Results: 42 studies were selected for the systematic review (SR), and 31 of them were also included in one of the meta-analyses. The pooled prevalence of OCD among ASD youth samples (n = 8916, mean age = 10.6 ± 1.6; 16.4% female) was 11.6% (95% confidence intervals [CI] = 6.9%; 18.8%), and the pooled prevalence of ASD among OCD children and adolescent samples (n = 6209, mean age = 14.1 ± 1.4; 45.7% female) was 9.5% (95% CI = 6.0%; 14.7%). Meta-regressions found a statistically higher prevalence of ASD among samples with a lower prevalence of females (β = −4.7; 95%CI = −8.6; −0.8). Children with both OCD and ASD present higher rates of functional impairment, psychopathology, and other comorbidities, compared to youth with either of the disorders alone. Conclusions: OCD and ASD are highly concurrent conditions in youth, with symptomatic, prognostic, severity, and therapeutic implications. Future research should focus on conducting longitudinal cohort studies prospectively to determine development trajectories, along with randomized controlled trials to assess the efficacy of specific therapeutic interventions.